Dried blood spots in bioanalysis of antimalarials: relevance and challenges in quantitative assessment of antimalarial drugs. (September 2013) - Taneja, Isha; Erukala, Madhuri; Raju, Kanumuri Siva Rama; Singh, Sheelendra Pratap; Wahajuddin
Malaria is the leading parasitic disease in emerging countries. Therapeutic drug monitoring of antimalarial drugs is becoming increasingly important due to their spreading resistance. Measuring systemic antimalarial drug concentrations is also vital for safety and PK evaluations during clinical development. The dried blood spot (DBS) technique is a convenient alternative sample-collection method to venipuncture, especially in resource -limited areas where the clinical studies of antimalarials are usually carried out. Various bioanalytical methods for antimalarial drug estimation utilizing DBS sampling have been reported. This review discusses the applicability and relevance of DBS in quantitative assessment of antimalarial drugs, the advantages and drawbacks of DBS, and the difficulties encountered during its implementation.